Nanofiber filled resin composition as well as preparation method and application thereof

By using nano -fiber -filled resin compositions in the printing line board (PCB) material, the problem of insufficient thermal performance, high thermal expansion coefficient, and low elastic modulus of existing materials, low thermal conductivity, reduced thermal expansion coefficient, and decreased thermal expansion coefficients. The improvement of elastic modulus enhances the stability and reliability of electronic equipment.

CN119371605APending Publication Date: 2025-01-28NANYA NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411373373.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing printed circuit board (PCB) materials have problems such as insufficient thermal performance, high thermal expansion coefficient and low elastic modulus in high performance and miniaturized electronic devices, which affect the stability and reliability of the equipment.

Method used

Using nano -fiber -filled resin compositions, resin is modified by high -length -length -diameter -ratio -ratio -ratio -ratio -ratio -in -law (such as alumina, aluminum nitride, and boron nanomium nanofiber) Elastic modulus.

Benefits of technology

It significantly improves the impact resistance, stretching strength, thermal conductivity, low thermal expansion coefficient and high elastic modulus of composite materials. It is suitable for covering metal foil layer pressure plates, enhancing the performance and reliability of electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a nanofiber filled resin composition as well as a preparation method and application thereof, and relates to the technical field of resin materials, the nanofiber filled resin composition comprises the following components in parts by weight: 50-200 parts of inorganic nanofiber, 60-120 parts of a resin composition, 15-25 parts of a cross-linking agent and 0.2-3 parts of an initiator; wherein the average diameter of the inorganic nanofibers is 1-8 nm, and the average length of the inorganic nanofibers is 0.5-15 [mu] m. The inorganic nanofibers with high length-diameter ratio are combined with the resin, and the nanofibers are uniformly dispersed in the resin composition as a filling agent and are cured in the presence of an initiator and a cross-linking agent; the prepreg and the metal foil-clad laminated board prepared from the prepreg not only have excellent impact resistance and excellent tensile strength, but also have high heat-conducting property, low thermal expansion coefficient and high elastic modulus.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of resin materials, and in particular to a nanofiber-filled resin composition and a preparation method and application thereof. Background Art

[0002] Printed circuit boards (PCBs) play a vital role in modern electronic devices. They are not only the support for electronic components, but also the bridge for electrical connections between components. As electronic devices develop towards high performance and miniaturization, the thermal performance of printed circuit boards (PCBs) becomes particularly important.

[0003] High thermal conductivity ensures effective heat conduction and keeps the operating temperature of electronic components within a safe range, thereby extending the service life of the equipment. At the same time, low thermal expansion coefficient is also crucial, which can reduce the dimensional changes of materials caused by temperature changes and ensure the stability and reliability of PCB in temperature fluctuation environments. In addition, high elastic modulus can provide better mechanical stability, making PCB less likely to deform when subjected to external forces, ensuring precise connection between components. Therefore, the development of PCB materials with high thermal conductivity, low thermal expansion coefficient and high elastic modulus is of great significance to improving the performance and reliability of electronic products.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] One of the objects of the present invention is to provide a nanofiber-filled resin composition which not only has excellent mechanical properties such as impact resistance and outstanding tensile strength, but also has the advantages of high thermal conductivity, low thermal expansion coefficient and high elastic modulus.

[0006] The second object of the present invention is to provide a method for preparing a nanofiber-filled resin composition, which has a simple process, high efficiency and is suitable for industrial mass production.

[0007] The third object of the present invention is to provide an application of a nanofiber-filled resin composition, which is beneficial to improving the mechanical properties of metal-clad laminates such as impact resistance and tensile strength, and is also beneficial to giving the metal-clad laminates advantages such as high thermal conductivity, low thermal expansion coefficient and high elastic modulus.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] In a first aspect, a nanofiber-filled resin composition comprises the following components in parts by weight:

[0010] 50-200 parts of inorganic nanofibers, 60-120 parts of resin composition, 15-25 parts of crosslinking agent, and 0.2-3 parts of initiator;

[0011] The inorganic nanofibers have an average diameter of 1 nm to 8 nm and an average length of 0.5 um to 15 um.

[0012] Further, the inorganic nanofibers include at least one of aluminum oxide nanofibers, aluminum nitride nanofibers and boron nitride nanofibers;

[0013] Preferably, the average volume particle size of the inorganic nanofibers is 400 nm. 3 -7.5×10 5 nm 3 .

[0014] Furthermore, the resin composition includes at least one of a bismaleimide resin and a cyanate ester resin.

[0015] Furthermore, the bismaleimide resin has a structure shown in formula (I):

[0016]

[0017] R1 is selected from any one or a combination of two or more of the following structures:

[0018]

[0019] R2 is selected from any one or a combination of two or more of the following structures:

[0020]

[0021] Furthermore, the cyanate resin includes at least one of a novolac cyanate resin, a bisphenol A cyanate resin and a tetramethyl bisphenol F cyanate resin.

[0022] Further, the crosslinking agent includes at least one of a diene compound, an acenaphthylene compound, a trialkenyl isocyanurate compound, a multifunctional acrylate compound, a multifunctional methacrylate compound, a multifunctional vinyl compound and a divinylbenzene compound;

[0023] Preferably, the initiator comprises at least one of dicumyl peroxide, di-tert-butyl peroxide, benzoyl peroxide, tert-butyl perbenzoate, dicyclohexyl peroxydicarbonate, cumene hydroperoxide and azobisisobutyronitrile.

[0024] Further, the component also includes at least one of a flame retardant and a toughening agent;

[0025] Preferably, the weight proportion of the flame retardant is 10-30 parts;

[0026] Preferably, the weight proportion of the toughening agent is 5 to 12 parts;

[0027] Preferably, the flame retardant comprises at least one of decabromodiphenylethane, decabromodiphenyl ether, octabromodiphenyl ether, ethylenebistetrabromophthalimide and tris(tribromophenyl)isocyanurate;

[0028] Preferably, the toughening agent comprises at least one of styrene-butadiene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer and maleic anhydride grafted styrene-butadiene-styrene block copolymer elastomer.

[0029] In a second aspect, a method for preparing the nanofiber-filled resin composition described in any one of the above items comprises the following steps:

[0030] The components are mixed in proportion to obtain the nanofiber-filled resin composition.

[0031] Furthermore, the method for preparing the inorganic nanofibers comprises the following steps:

[0032] Spinning the precursor sol to obtain shaped fibers, and calcining the shaped fibers to obtain the inorganic nanofibers;

[0033] Preferably, the spinning method includes centrifugal spinning;

[0034] Preferably, the spinning further comprises a drying step;

[0035] Preferably, the calcination process comprises the following steps:

[0036] First, calcination is performed at a temperature of 100°C-200°C, then calcination is performed at a temperature of 400°C-600°C, and then calcination is performed at a temperature of 1000°C-1200°C.

[0037] In a third aspect, a use of the nanofiber-filled resin composition described in any one of the above items in the preparation of a metal-clad laminate for a printed circuit board.

[0038] Compared with the prior art, the present invention has at least the following beneficial effects:

[0039] The nanofiber-filled resin composition provided by the present invention modifies the organic resin by using inorganic nanofibers with a high aspect ratio (as fillers), thereby significantly improving the overall performance of the composite material. Specifically, inorganic nanofibers with an average diameter of 1nm-8nm and an average length of 0.5um-15um are uniformly dispersed in the organic resin. After being cured by an initiator and a cross-linking agent, the resulting composite material not only has excellent mechanical properties such as impact resistance and outstanding tensile strength, but also has the advantages of high thermal conductivity, low thermal expansion coefficient, high elastic modulus, etc. under the coordinated cooperation of various components and their weight ratios.

[0040] The method for preparing the nanofiber-filled resin composition provided by the invention has simple process and high efficiency and is suitable for industrialized batch production.

[0041] The application of the nanofiber-filled resin composition provided by the present invention is beneficial to improving the mechanical properties of the metal-clad laminate such as impact resistance and tensile strength, and is also beneficial to giving the metal-clad laminate advantages such as high thermal conductivity, low thermal expansion coefficient and high elastic modulus. DETAILED DESCRIPTION

[0042] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] According to a first aspect of the present invention, there is provided a nanofiber-filled resin composition comprising the following components in parts by weight:

[0044] 50-200 parts of inorganic nanofibers, 60-120 parts of resin composition, 15-25 parts of crosslinking agent, and 0.2-3 parts of initiator;

[0045] Among them, the average diameter of the inorganic nanofibers is 1nm-8nm, and the average length is 0.5um-15um.

[0046] It should be noted that inorganic nanofibers are widely used due to their unique physical and chemical properties. They have high specific surface area, excellent mechanical properties and good thermal stability, and are therefore ideal reinforcing materials for composite materials. In the present invention, inorganic nanofibers are filled into the resin composition to improve the overall performance of the resin material.

[0047] In the present invention, the typical but non-limiting average diameter of the inorganic nanofibers is, for example, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, and 8 nm, and the typical but non-limiting average length of the inorganic nanofibers is, for example, 0.5 um, 1 um, 2 um, 3 um, 4 um, 5 um, 6 um, 7 um, 8 um, 9 um, 10 um, 11 um, 12 um, 13 um, 14 um, and 15 um. In the present invention, the inorganic nanofibers (as fillers) with suitable aspect ratios are used to modify the organic resin, which can significantly improve the overall performance of the composite material; if the aspect ratio of the inorganic nanofibers is too small, it will cause an increase in fiber endpoints, thereby forming more stress concentration areas inside the material, reducing the ability of the material to withstand external forces; if the aspect ratio of the inorganic nanofibers is too large, it will cause the fibers to be difficult to disperse evenly in the resin, thereby easily generating stress concentration areas, and reducing the overall mechanical properties of the material.

[0048] In the present invention, the typical but non-limiting weight fractions of inorganic nanofibers are, for example, 50 parts, 100 parts, 150 parts, and 200 parts; the typical but non-limiting weight fractions of resin composition are, for example, 60 parts, 80 parts, 100 parts, and 120 parts; the typical but non-limiting weight fractions of crosslinking agent are, for example, 15 parts, 20 parts, and 25 parts; the typical but non-limiting weight fractions of initiator are, for example, 0.2 parts, 0.5 parts, 1 parts, 2 parts, and 3 parts. With the coordinated coordination of the components and their weight ratios, the overall performance of the composite material can be fully improved.

[0049] In summary, the nanofiber-filled resin composition provided by the present invention modifies the organic resin by using inorganic nanofibers with a high aspect ratio (as fillers), thereby significantly improving the overall performance of the composite material. Specifically, inorganic nanofibers with an average diameter of 1nm-8nm and an average length of 0.5um-15um are uniformly dispersed in the organic resin. After being cured by an initiator and a cross-linking agent, the resulting composite material not only has excellent mechanical properties such as impact resistance and outstanding tensile strength, but also has the advantages of high thermal conductivity, low thermal expansion coefficient and high elastic modulus, etc., under the synergistic coordination of the components and their weight ratios.

[0050] In a preferred embodiment, the inorganic nanofibers include but are not limited to at least one of aluminum oxide nanofibers, aluminum nitride nanofibers and boron nitride nanofibers.

[0051] In the present invention, the average volume particle size of the inorganic nanofibers can be 400 nm. 3 -7.5×10 5 nm 3 , which is more conducive to ensuring that the mechanical properties of the composite materials are fully improved, and is more conducive to ensuring the advantages of high thermal conductivity, low thermal expansion coefficient and high elastic modulus.

[0052] In a preferred embodiment, the resin composition includes but is not limited to at least one of a bismaleimide resin and a cyanate resin. The thermosetting BT resin obtained by mixing the bismaleimide resin and the cyanate resin has the advantages of a high glass transition temperature, a low dielectric constant, and a high mechanical strength.

[0053] In the present invention, the bismaleimide resin has a structure shown in formula (I):

[0054]

[0055] R1 can be selected from any one or a combination of two or more of the following structures:

[0056]

[0057] R2 can be selected from any one or a combination of two or more of the following structures:

[0058]

[0059] In a preferred embodiment, the cyanate ester resin includes but is not limited to at least one of a novolac cyanate ester resin, a bisphenol A cyanate ester resin and a tetramethyl bisphenol F cyanate ester resin.

[0060] In a preferred embodiment, the crosslinking agent includes but is not limited to at least one of diene compounds, acenaphthylene compounds, trialkenyl isocyanurate compounds, multifunctional acrylate compounds, multifunctional methacrylate compounds, multifunctional vinyl compounds and divinylbenzene compounds.

[0061] The cross-linking agent used in the present invention can effectively promote the cross-linking reaction of the resin, fully improve the cross-linking density of the resin, and is conducive to forming a more stable three-dimensional network structure, thereby improving the glass transition temperature, toughness, heat resistance and solvent resistance of the cured material, which makes the material have a lower dielectric constant and dielectric loss when applied to metal-clad plates.

[0062] In a preferred embodiment, the initiator includes but is not limited to at least one of dicumyl peroxide, di-tert-butyl peroxide, benzoyl peroxide, tert-butyl perbenzoate, dicyclohexyl peroxydicarbonate, cumene hydroperoxide and azobisisobutyronitrile. The above initiators can cooperate with the crosslinking agent to fully promote the curing of the components.

[0063] In a preferred embodiment, the components of the present invention further include at least one of a flame retardant and a toughening agent.

[0064] In the present invention, the weight proportion of the flame retardant can be 10 parts to 30 parts, and its typical but non-limiting weight proportion is, for example, 10 parts, 15 parts, 20 parts, 25 parts, and 30 parts; the weight proportion of the toughening agent can be 5 parts to 12 parts, and its typical but non-limiting weight proportion is, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, and 12 parts.

[0065] In a preferred embodiment, the flame retardant includes, but is not limited to, at least one of decabromodiphenylethane, decabromodiphenyl ether, octabromodiphenyl ether, ethylenebistetrabromophthalimide and tris(tribromophenyl)isocyanurate.

[0066] In a preferred embodiment, the toughening agent includes but is not limited to at least one of styrene-butadiene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer and maleic anhydride grafted styrene-butadiene-styrene block copolymer elastomer.

[0067] According to a second aspect of the present invention, there is provided a method for preparing the nanofiber-filled resin composition as described above, comprising the following steps:

[0068] The components are mixed in proportion to obtain a nanofiber-filled resin composition.

[0069] The method for preparing the nanofiber-filled resin composition provided by the invention has simple process and high efficiency and is suitable for industrialized batch production.

[0070] In the present invention, the resin composition, the flame retardant, the cross-linking agent, the toughening agent, the initiator, the inorganic nanofibers and the solvent are fully mixed according to proportions to obtain the nanofiber-filled resin composition.

[0071] In a preferred embodiment, the solvent includes but is not limited to at least one of toluene, butanone, acetone, dimethylformamide, methyl ethyl ketone and propylene glycol methyl ether.

[0072] In a preferred embodiment, the method for preparing inorganic nanofibers comprises the following steps:

[0073] The precursor sol is spun to obtain shaped fibers, and the shaped fibers are calcined to obtain inorganic nanofibers.

[0074] In the present invention, alumina nanofibers can be prepared using a mixture of aluminum propoxide and aluminum nitrate as a precursor, aluminum nitride nanofibers can be prepared using a mixture of aluminum chloride and urea as a precursor, and boron nitride nanofibers can be prepared using a mixture of boric acid and melamine as a precursor.

[0075] In a preferred embodiment, the spinning method includes but is not limited to centrifugal spinning; and a drying step is also included after spinning.

[0076] In the present invention, the solution-gel method combined with the electrostatic spinning method can be used to prepare inorganic nanofibers, including the following steps: dissolving the precursor in distilled water, heating and refluxing at a temperature of 60°C-80°C under the action of a catalyst and a spinning aid, evaporating and concentrating to obtain a precursor sol; then, at a temperature of 25°C-30°C and a relative humidity of 65%-75%, the sol is drawn into a fiber shape using centrifugal spinning technology, and then dried at a temperature of 25°C-40°C and a relative humidity of 45%-65% to remove moisture and volatile components therein; finally, the formed fiber is calcined.

[0077] In a preferred embodiment, the calcination process of the present invention comprises the following steps:

[0078] First, calcination is performed at a temperature of 100°C-200°C, then calcination is performed at a temperature of 400°C-600°C, and then calcination is performed at a temperature of 1000°C-1200°C.

[0079] First, it is calcined at 100°C-200°C to remove residual moisture and organic components, then calcined at 400°C-600°C to transform the fibers from amorphous state into regular nanofibers, and finally calcined at 1000°C-1200°C to transform them into stable nanofibers.

[0080] The preparation method of the inorganic nanofibers of the present invention is conducive to preparing inorganic nanofibers with an average diameter of 1nm-8nm, an average length of 0.5um-15um and consistent fiber length. The nanofibers have the performance of a high aspect ratio. They are combined with resin as a filling material, thereby significantly improving the overall performance of the composite material.

[0081] A typical method for preparing a nanofiber-filled resin composition comprises the following steps:

[0082] Step 1: preparing the nanofiber precursor through sol preparation, fiber forming, drying and high-temperature calcination to obtain inorganic nanofibers as fillers;

[0083] Step 2: fully stirring and mixing the resin composition, crosslinking agent, toughening agent and solvent until the resin is completely dissolved, with the stirring speed being 1000rpm-1500rpm, to obtain a precursor mixed solution;

[0084] Step 3: Add the flame retardant and inorganic nanofibers to the precursor mixed solution obtained in step 2 and stir and mix thoroughly at a stirring speed of 1000 rpm-1500 rpm, then add the initiator and mix thoroughly, and then homogenize and discharge to obtain a nanofiber-filled resin composition.

[0085] According to a third aspect of the present invention, there is provided a use of any of the above-mentioned nanofiber-filled resin compositions in the preparation of metal-clad laminates for printed circuit boards.

[0086] In the present invention, the preparation method of the metal foil-clad laminate comprises the following steps: dispersing the nanofiber-filled resin composition in the glass fiber cloth through an impregnation process, and then baking and curing to obtain a semi-cured sheet, and then superimposing the semi-cured sheet with the metal foil, and pressing at high temperature under vacuum conditions to obtain the metal foil-clad laminate.

[0087] The application of the nanofiber-filled resin composition provided by the present invention is beneficial to improving the mechanical properties of the metal-clad laminate such as impact resistance and tensile strength, and is also beneficial to giving the metal-clad laminate advantages such as high thermal conductivity, low thermal expansion coefficient and high elastic modulus.

[0088] After the bismaleimide resin and the cyanate resin are mixed and dissolved in a solvent, inorganic nanofibers are added as fillers, flame retardants, toughening agents, crosslinking agents and initiators to mix and obtain a resin glue, and the resin glue is combined with a glass fiber cloth reinforcement material (gluing), and then cured by baking to obtain a prepreg. In the present invention, the resin glue can be prepared at room temperature, which can greatly shorten the preparation time and improve production efficiency. In the preparation of the prepreg, the shortcomings of the slow curing rate, curing temperature and curing time of a single resin are compensated. In the present invention, the preparation of the prepreg can be completed at a temperature of 140°C-160°C and a time of 200s-300s; the prepreg is then laminated to obtain a metal foil-clad laminate with excellent performance, which can be used for printed circuit boards.

[0089] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0090] Examples 1-5

[0091] Examples 1-5 provide a nanofiber-filled resin composition, and the components and their proportions are shown in Table 1.

[0092] Alumina nanofibers are synthesized by the following steps: aluminum isopropoxide and aluminum nitrate are dissolved in distilled water, and glacial acetic acid and lactic acid are added as catalysts and spinning aids; the mixture is gradually converted into a viscous sol state by heating reflux and evaporation concentration; then, the sol is drawn into a fiber shape by centrifugal spinning technology at a temperature of 25°C and a relative humidity of 70%, and then dried at a temperature of 35°C and a relative humidity of 55%; after drying, it is first calcined at a temperature of 150°C to remove residual moisture and organic components, and then calcined at a temperature of 500°C to convert the fibers from an amorphous state into regular alumina nanofibers, and finally calcined at a temperature of 1100°C to convert them into stable alumina nanofibers, and the average diameter of the obtained nanofibers is 5nm and the average length is 8um.

[0093] Boron nitride nanofibers are synthesized by the following steps: dissolving boric acid and melamine in distilled water, adding acetic acid and lactic acid as catalysts and spinning aids; the mixture is gradually converted into a viscous sol state by heating reflux and evaporation concentration; then, at a temperature of 25°C and a relative humidity of 70%, the sol is drawn into a fiber shape by centrifugal spinning technology, and then dried at a temperature of 35°C and a relative humidity of 55%; after drying, it is first calcined at a temperature of 150°C to remove residual moisture and organic components, and then calcined at a temperature of 500°C to convert the fiber from an amorphous state into a regular boron nitride nanofiber, and finally calcined at a temperature of 1100°C to convert it into a stable boron nitride nanofiber, and the average diameter of the obtained nanofiber is 5nm and the average length is 8um.

[0094] The structural formulas of bismaleimide resin, compound B1 and compound B2 (n is a positive integer of ≥1) are as follows:

[0095]

[0096]

[0097] The method for preparing the nanofiber-filled resin composition in the above embodiment comprises the following steps:

[0098] S1: Add butanone and toluene into the reactor, turn on the high-speed stirrer, set the speed to 1500 rpm, continue stirring and control the temperature at 45°C;

[0099] S2: Add bismaleimide resin, cyanate resin, crosslinking agent and toughening agent into the reaction kettle, and continue stirring for 60 minutes after the addition is completed to completely dissolve the resin;

[0100] S3: Add flame retardant and inorganic nanofiber (filler) into the reactor, turn on the high-speed stirrer, set the speed to 1800 rpm, and continue stirring for 60 minutes after the addition is completed to fully mix;

[0101] S4: Add initiator to the reactor. After adding, start cooling water circulation and keep stirring at 1500 rpm and 45°C for 180 minutes, then discharge.

[0102] Table 1

[0103]

[0104] Example 6

[0105] This embodiment provides a nanofiber-filled resin composition, which is different from Embodiment 1 in that the average diameter of the alumina nanofibers used in this embodiment is 1 nm and the average length is 0.5 um;

[0106] The remaining components and their proportions are the same as those in Example 1.

[0107] Example 7

[0108] This embodiment provides a nanofiber-filled resin composition, which is different from Embodiment 1 in that the average diameter of the alumina nanofibers used in this embodiment is 5 nm and the average length is 0.5 um;

[0109] The remaining components and their proportions are the same as those in Example 1.

[0110] Example 8

[0111] This embodiment provides a nanofiber-filled resin composition, which is different from Embodiment 1 in that the average diameter of the alumina nanofibers used in this embodiment is 5 nm and the average length is 15 um;

[0112] The remaining components and their proportions are the same as those in Example 1.

[0113] Example 9

[0114] This embodiment provides a nanofiber-filled resin composition, which is different from Embodiment 1 in that the average diameter of the alumina nanofibers used in this embodiment is 8 nm and the average length is 15 um;

[0115] The remaining components and their proportions are the same as those in Example 1.

[0116] Example 10

[0117] This embodiment provides a nanofiber-filled resin composition, which differs from Embodiment 1 in that no cyanate resin is added in this embodiment;

[0118] The remaining components and their proportions are the same as those in Example 1.

[0119] Comparative Examples 1-3

[0120] Comparative Examples 1-3 provide a nanofiber-filled resin composition, the components and their proportions are shown in Table 2, and the preparation method is referred to in Example.

[0121] Table 2

[0122]

[0123] Comparative Example 4

[0124] This comparative example provides a nanofiber-filled resin composition, which differs from Example 1 in that the average diameter of the aluminum oxide nanofibers used in this example is 10 nm;

[0125] The remaining components and their proportions are the same as those in Example 1.

[0126] Compared with Example 1, the defect of this comparative example is that the impact strength and tensile strength of the obtained material are too low.

[0127] Comparative Example 5

[0128] This comparative example provides a nanofiber-filled resin composition, which differs from Example 1 in that the average length of the aluminum oxide nanofibers used in this example is 18 um;

[0129] The remaining components and their proportions are the same as those in Example 1.

[0130] Compared with Example 1, the defect of this comparative example is that the mechanical properties and dielectric properties of the obtained material are relatively low.

[0131] Test example

[0132] Semi-cured sheets were prepared using the nanofiber-filled resin compositions obtained in Examples 1-10 and Comparative Examples 1-5, and the semi-cured sheets were then laminated with metal foil to obtain metal foil-clad laminates. The obtained metal foil-clad laminates were respectively recorded as Sample 1, Sample 2, Sample 3, Sample 4, Sample 5, Sample 6, Sample 7, Sample 8, Sample 9, Sample 10, Comparative Sample 1, Comparative Sample 2, Comparative Sample 3, Comparative Sample 4 and Comparative Sample 5.

[0133] The preparation process of the prepreg is as follows:

[0134] Use 2116E-glass fiberglass cloth for gluing and baking;

[0135] The gluing baking temperature is 140℃-160℃, and the gluing speed is 10m / min.

[0136] The preparation process of metal foil laminate is as follows:

[0137] The metal foil used is RTF copper foil;

[0138] Lamination conditions: vacuum pressure 50 Torr; pressure 1.2 MPa-1.5 MPa; hot plate temperature 150°C-220°C; curing time 200 min.

[0139] The obtained metal foil clad laminate was subjected to the following performance tests:

[0140] (I) Tensile strength: According to the standard of IPC-TM-650 2.2.1, the tensile strength of the sample is tested using a universal mechanical testing machine;

[0141] (ii) Impact strength: According to the standard of IPC-TM-650 2.4.23, the tensile strength of the sample is tested using a tensile impact testing machine;

[0142] (iii) Elastic modulus: The elastic modulus of the sample shall be measured using a DMA instrument in accordance with the standards specified in IPC-TM-650 2.4.24.4;

[0143] (iv) Thermal expansion coefficient: The thermal expansion coefficient of the sample shall be measured using a TMA instrument in accordance with the standards specified in IPC-TM-650 2.4.24;

[0144] (V) Dielectric constant (D k ) and dielectric loss factor (D f ): The dielectric constant and dielectric loss factor test methods are in accordance with the test specified in IPC-TM-650 2.5.5.9;

[0145] (VI) Thermal conductivity: The thermal conductivity of the sample shall be measured using a thermal conductivity tester in accordance with the standards specified in IPC-TM-650 2.4.50;

[0146] (VII) PCT: The samples were subjected to a cooking test in a pressure cooker. After the plates were continuously cooked in a pressure cooker at 0.105 MPa and 120°C for 120 min, they were immersed in a 288°C tin furnace to observe the delamination and blistering time. Samples with a delamination time of less than 5 min were evaluated as ×, and samples with a delamination time of more than 5 min and less than 10 min were evaluated as ○;

[0147] The above performance test results are shown in Table 3 and Table 4. Table 3

[0148]

[0149] Table 4

[0150]

[0151] It can be seen from the data in Tables 3 and 4 that the present invention uses inorganic nanofibers with an average diameter of 1nm-8nm and an average length of 0.5um-15um as fillers, uniformly disperses them in an organic resin, and cures them in the presence of an initiator and a cross-linking agent. The resulting semi-cured sheet and the metal foil-clad laminate prepared by stacking the semi-cured sheet and the metal foil have improved mechanical properties of impact resistance and tensile strength, and also have high thermal conductivity, low thermal expansion coefficient and high elastic modulus.

[0152] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A nanofiber-filled resin composition, characterized in that: It includes the following components by weight: 50-200 parts of inorganic nanofibers, 60-120 parts of resin composition, 15-25 parts of crosslinking agent, and 0.2-3 parts of initiator; The inorganic nanofibers have an average diameter of 1 nm to 8 nm and an average length of 0.5 um to 15 um.

2. The nanofiber-filled resin composition according to claim 1, characterized in that: The inorganic nanofibers include at least one of aluminum oxide nanofibers, aluminum nitride nanofibers and boron nitride nanofibers; Preferably, the average volume particle size of the inorganic nanofibers is 400 nm. 3 -7.5×10 5 nm 3 .

3. The nanofiber-filled resin composition according to claim 1, characterized in that: The resin composition includes at least one of a bismaleimide resin and a cyanate ester resin.

4. The nanofiber-filled resin composition according to claim 3, characterized in that: The bismaleimide resin has a structure shown in formula (I): R1 is selected from any one or a combination of two or more of the following structures: R2 is selected from any one or a combination of two or more of the following structures:

5. The nanofiber-filled resin composition according to claim 3, characterized in that: The cyanate resin includes at least one of a novolac cyanate resin, a bisphenol A cyanate resin, and a tetramethyl bisphenol F cyanate resin.

6. The nanofiber-filled resin composition according to claim 1, characterized in that: The cross-linking agent includes at least one of a diene compound, an acenaphthylene compound, a trialkenyl isocyanurate compound, a multifunctional acrylate compound, a multifunctional methacrylate compound, a multifunctional vinyl compound, and a divinylbenzene compound; Preferably, the initiator comprises at least one of dicumyl peroxide, di-tert-butyl peroxide, benzoyl peroxide, tert-butyl perbenzoate, dicyclohexyl peroxydicarbonate, cumene hydroperoxide and azobisisobutyronitrile.

7. The nanofiber-filled resin composition according to claim 1, characterized in that: The components also include at least one of a flame retardant and a toughening agent; Preferably, the weight proportion of the flame retardant is 10-30 parts; Preferably, the weight proportion of the toughening agent is 5 to 12 parts; Preferably, the flame retardant comprises at least one of decabromodiphenylethane, decabromodiphenyl ether, octabromodiphenyl ether, ethylenebistetrabromophthalimide and tris(tribromophenyl)isocyanurate; Preferably, the toughening agent comprises at least one of styrene butadiene block copolymer, hydrogenated styrene butadiene styrene block copolymer and maleic anhydride grafted styrene butadiene styrene block copolymer elastomer.

8. A method for preparing the nanofiber-filled resin composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: The components are mixed in proportion to obtain the nanofiber-filled resin composition.

9. The preparation method according to claim 8, characterized in that: The method for preparing the inorganic nanofibers comprises the following steps: Spinning the precursor sol to obtain shaped fibers, and calcining the shaped fibers to obtain the inorganic nanofibers; Preferably, the spinning method includes centrifugal spinning; Preferably, the spinning further comprises a drying step; Preferably, the calcination process comprises the following steps: First, calcination is performed at a temperature of 100°C-200°C, then calcination is performed at a temperature of 400°C-600°C, and then calcination is performed at a temperature of 1000°C-1200°C.

10. Use of the nanofiber-filled resin composition according to any one of claims 1 to 7 in the preparation of a metal-clad laminate for a printed circuit board.